EP611 Microcytic elongated and fragmented (MELF) pattern in early-stage endometrioid adenocarcinoma – is there association with vaginal recurrence? A case report. (1st November 2019) - Sá, I; Rocha, AC; Raposo, S; Sousa, R; Abrantes, C; Sá, L
Abstract : Introduction/Background: Prognosis of early-stage endometrial adenocarcinoma is favourable. However, some factors can influence the risk of recurrence: tumour size and grade, depth of myometrial invasion, cervical stromal involvement and lympho-vascular space invasion (LVSI). A microcytic, elongated, and fragmented (MELF) pattern of invasion has also been implicated in poor prognosis. Many studies had describe the association between MELF pattern with non-vaginal recurrences and lymph-node metastases. Methodology: This case describe an early-stage MELF pattern endometrial adenocarcinoma with no LVSI and multiple vaginal recurrences. Results: A 74-year-old woman with hypertension and history of cerebral aneurysm was referred to our institution for an endometrial adenocarcinoma G1 diagnosed in a previous biopsy. A total abdominal hysterectomy and bilateral salpingo-oophorectomy was performed (due to her comorbidities, we didn't accomplish bilateral pelvic lymphadenectomy). Histologic diagnosis revealed an endometrioid adenocarcinoma G2, with myometrial invasion depth >50%, negative LVSI, MELF pattern of myometrial invasion and negative peritoneal washing cytology - FIGO stage IB. One month later, the patient referred vaginal bleeding and presented a vaginal vault vegetant lesion measuring 1, 5 cm. The biopsy showed metastasis of endometrioid adenocarcinoma. She was submitted to a full lesion resection and started adjuvant vaginal brachytherapy (50 Gy/5 fractions). Four months later, she presented with 2 vaginal vault milimetric lesions whose biopsy revealed metastases of adenocarcinoma. The complete resection of the lesions confirmed the diagnosis. She repeated vaginal brachytherapy treatment (30Gy/5fractions). Pelvic MRI didn't show lymph-node metastases. The patient remains in clinical control in our institution. Conclusion: The significance of MELF pattern is still unclear. Although many studies describe its association with lymph node metastases and non-vaginal recurrences, this case shows that this histologic pattern can also be associated to vaginal metastases. In the future, MELF pattern could be useful for identifying patients in early-stage endometrial tumours with higher risk of recurrence. Disclosure: Nothing to disclose.